2022
DOI: 10.1039/d2cp01392d
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of ammonia on free-standing and epitaxial hexagonal boron nitride

Abstract: We report a thermodynamically feasible mechanism for producing H2 from NH3 using hBN as a catalyst. 2D catalysts have exceptional surface areas with unique thermal and electronic properties suited for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…1. The structure and properties of V B and V N vacancies have been discussed in detail in previous work and are shown in b and c. 56 V N is more stable than V B with E f of 8.63 eV and 9.75 eV, respectively. V B has C 2v symmetry, whereas V N has D 3h symmetry due to Jahn-Teller distortion.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1. The structure and properties of V B and V N vacancies have been discussed in detail in previous work and are shown in b and c. 56 V N is more stable than V B with E f of 8.63 eV and 9.75 eV, respectively. V B has C 2v symmetry, whereas V N has D 3h symmetry due to Jahn-Teller distortion.…”
Section: Resultsmentioning
confidence: 92%
“…54,55 We have previously reported that HV B vacancies can be effectively produced by exposing boron-nitrogen divacancies to ammonia. 56 Furthermore, as hydrogen atoms are ordinarily contained in hBN precursors, HV B defects are likely to be generated during hBN processing, such as during the growth of hBN nanowalls. 57 Previous work by Nash et al 58 investigated HV B defects as active sites for the hydrogenation of alkenes on metal-free hBN.…”
Section: Introductionmentioning
confidence: 99%
“…For example, h-BN performs well for the adsorption of biomolecules flavonoids, and battery-active materials, 28,29 and it proves feasible thermodynamically to produce H 2 from NH 3 by using h-BN as the catalyst. 30 Additionally, the monovacancies, such as the vacancy of boron (V B ) and the vacancy of nitrogen (V N ), have been easily obtained in the h-BN monolayers or nanotube synthesis. [31][32][33][34] Confining the metal atom on such defects will have strong interactions which lead to stabilizing the SACs with enhanced catalytic activity.…”
Section: Introductionmentioning
confidence: 99%